ANALISIS KEBUTUHAN MODAL KERJA DITINJAU DARI TINGKAT PERPUTARAN OPERASI PERUSAHAAN PADA PDAM KABUPATEN BANYUMAS PURBALINGGA DAN BANJARNEGARA - Lestari, Sri; Widyastuti, Umi; Sarwin, Sarwin (Faculty of Economics and Business Universitas Jenderal Soedirman, 2007)
Basically the meaning of working capital is the capital needed by the company to finance company’s operation daily. The need of working capital for a company can be reflected from it’s sales scale volume. By the sales scale volume owned by the company, the activity level of company’s operation can be determined.The aims of research are first to analyze the tendence of working capital turnover development level observed from sales level and the tendency of working capital need observed from company’s operation turnover level at Drinking Water Loco Company of Banyumas, purbalingga and Banjarnegara Regency. It is Limited on company’s functional working capital which includes working capital elements, they are cash, inventory and account receivable. The data collected includes six year data, that is from 2000 till 2005.As the result of the research, it can be concluded that working capital turnover at PDAM Banyumas, Purbalingga and banjarnegara Regency from 2000 till 2005 tends to reduce if be folowed the sales increase and the need of working capital tends at PDAM Banyumas, Purbalingga dan Banjarnegara Regency to increase.From this research, it can be implicated that PDAM Banyumas, Purbalingga and Banjarnegara Regency must effort working capital turnover periode isn’t too long and the third Regency must pay more attention on the size of its sales level in order to create sufficient amount of working capital need suitable with company’s activity level.